Pro Android Web Game Apps Using HTML5, CSS3 and JavaScript - Bura, Juriy; Coates, Paul (Apress : Imprint: Apress, 2012)
Dive into game development and create great multiplayer online games with Pro Android Web Game Apps. This hands-on guide covers both the theory and practice of browser game development for the Android platform. You'll use cutting-edge technologies to make game engines in your browser, establish real-time server communication, and create amazing gaming experiences with artificial intelligence and rich media. Bring your knowledge of HTML and JavaScript to the next level with Pro Android Web Game Apps. You are guided through exciting projects that give you firsthand experience with core game app development concepts. You'll start with a blank HTML page, and by the end of the book, have the skills needed to  create a multiplayer online game with rich graphics, sound, animation, and more-even if you have no previous games development or server-side experience.  .